OP0032 ERAP1-MEDIATED IMMUNOGENICITY AND IMMUNE-PHENOTYPES IN HLA-B51+ BEHÇET'S DISEASE POINT TO PATHOGENIC CD8 T CELL EFFECTOR RESPONSES. (2nd June 2020) - Al-Obeidi, A. F.; Cavers, A.; Ozguler, Y.; Manches, O.; Zhong, H.; Yurttas, B.; Ueberheide, B.; Hatemi, G.; Kugler, M.; Nowatzky, J.
Abstract : Background: HLA-B51 is a definite risk factor for Behçet's disease (BD). A coding variant of ERAP1, Hap10 – with low peptide-trimming activity – vastly potentiates this risk, but is mechanistically unclear 1, 2) . Objectives: To test the hypothesis that low or absent ERAP1 activity alters CD8 T cell immunogenicity through changes in the HLA-B51 peptidome and shapes the CD8 T cell immune response in affected subjects. Methods: We generated HLA-B51 + ERAP1 KO LCL clones using CRISPR-Cas9, performed mass spectrometry of the immunoprecipitated MHC-class I peptidome with subsequent computational deconvolution for HLA-B51-binding peptides. We then assessed single cell (ICS), bulk (ELISA) and proliferative (CFSE) CD8 effector (IFNg, granzyme B, perforin) T cell responses through stimulation of allogeneic donor cells with WT vs KO LCL and determined ERAP1 haplotypes in 49 untreated Turkish BD subjects with ocular and/ or major vascular involvement as well as healthy donors (HD) whose PBMC were profiled using 6 multicolour flow cytometry panels. Results: WT and KO peptidomes differed significantly (p<0.0005 Fisher's exact test) with a distinctive shift of peptide length frequencies exceeding 9-mer (binding optimum) in the KO vs WT. This held true for computationally deconvoluted HLA-B51 binders. IFNg secretion from CD8 T cells stimulated with KO LCL was significantly different from WT (ICS, p=0.0006; ELISA, p=0.0059) as were CD8 T cell proliferation and ICS of perforin/granzyme B + CD8 T cells. Analysis of 133 T, B, NK and monocyte cell populations revealed predominance of CD8 T and NKT cell subset in HLA-B51+/Hap10+ BD vs HLA-B51+/Hap10- BD and HD, accounting for 80% of all populations reaching significance (p<0.05, Mann-Whitney). Naive and effector memory CD8 T cell subsets were inversely correlated. Cohen's effect sizes were large (>0.8) or very large (>1.2). Conclusion: We show that absence of functional ERAP1 alters human CD8 T cell immunogenicity. This is mediated by an HLA-class I peptidome with propensity for longer peptides above 9mer and suggests loss or de-novo presentation of peptide-HLA-B51 complexes to cognate CD8 TCR. The reciprocal changes in antigen- experienced vs naive CD8 T cell subsets in affected subjects point to biologic significance of HLA-B51/Hap10 in BD. Collectively, our findings suggest that an altered HLA-B51 peptidome modulates immunogenicity of CD8 effector T cells in ERAP1-Hap10 carriers with BD and identify targets for future drug development. References: [1]Kirino, Y., G. Bertsias, Y. Ishigatsubo, N. Mizuki, I. Tugal-Tutkun, E. Seyahi, Y. Ozyazgan, F. S. Sacli, B. Erer, H. Inoko, Z. Emrence, A. Cakar, N. Abaci, D. Ustek, C. Satorius, A. Ueda, M. Takeno, Y. Kim, G. M. Wood, M. J. Ombrello, A. Meguro, A. Gul, E. F. Remmers, and D. L. Kastner. 2013. 'Genome-wide association analysis identifies new susceptibility loci for Behcet's disease and epistasis between HLA-B*51 and ERAP1', Nat Genet, 45: 202-7. [2]Takeuchi, M., M. J. Ombrello, Y. Kirino, B. Erer, I. Tugal-Tutkun, E. Seyahi, Y. Ozyazgan, N. R. Watts, A. Gul, D. L. Kastner, and E. F. Remmers. 2016. 'A single endoplasmic reticulum aminopeptidase-1 protein allotype is a strong risk factor for Behcet's disease in HLA-B*51 carriers', Ann Rheum Dis, 75: 2208-11. Disclosure of Interests: Arshed F. Al-Obeidi: None declared, Ann Cavers: None declared, Yesim Ozguler: None declared, Olivier Manches: None declared, Hua Zhong: None declared, Berna Yurttas: None declared, Beatrix Ueberheide: None declared, Gulen Hatemi Grant/research support from: BMS, Celgene Corporation, Silk Road Therapeutics – grant/research support, Consultant of: Bayer, Eli Lilly – consultant, Speakers bureau: AbbVie, Mustafa Nevzat, Novartis, UCB – speaker, Matthias Kugler: None declared, Johannes Nowatzky: None declared